2016
DOI: 10.1080/17513758.2016.1242784
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of an HIV latent infection model including both virus-to-cell infection and cell-to-cell transmission

Abstract: HIV can infect cells via virus-to-cell infection or cell-to-cell viral transmission. These two infection modes may occur in a synergistic way and facilitate viral spread within an infected individual. In this paper, we developed an HIV latent infection model including both modes of transmission and time delays between viral entry and integration or viral production. We analysed the model by defining the basic reproductive number, showing the existence, positivity and boundedness of the solution, and proving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…Model (6)- (11) assumes that, once the HIV contacts a CD4 + T cell, it becomes infected in the same time. Neglecting the time delays is an unrealistic assumption (see, e.g., [29,30]). The aim of this paper is to propose HIV infection models which improve model (6)-(11) by taking into account three time delays, discrete or distributed.…”
Section: U(t) = (1 -ε 1 )λ 3 χ S(t) P(t) -β 4 G 3 U(t) mentioning
confidence: 99%
“…Model (6)- (11) assumes that, once the HIV contacts a CD4 + T cell, it becomes infected in the same time. Neglecting the time delays is an unrealistic assumption (see, e.g., [29,30]). The aim of this paper is to propose HIV infection models which improve model (6)-(11) by taking into account three time delays, discrete or distributed.…”
Section: U(t) = (1 -ε 1 )λ 3 χ S(t) P(t) -β 4 G 3 U(t) mentioning
confidence: 99%
“…Alshorman et al [2] established the local and global stability of equilibria for system (1). Wang et al [55] further considered both the virus-to-cell infection and cell-to-cell transmission in system (1), and they also gave the proof of the local and global stability of equilibria as well as the persistence result.…”
Section: Yu Yang Yueping Dong and Yasuhiro Takeuchimentioning
confidence: 99%
“…Syncytium formation, an HIVinduced cell fusion, was recognized in the early 1990s (Callahan, 1994). Another type of cell-to-cell transmission through tight junctions was shown for HIV (Hübner et al, 2009;Wang et al, 2017) and murine leukemia virus (Sherer et al, 2010). Receptors on tight junctions that specifically recognize hepatitis C virus (Carloni et al, 2012;Ploss et al, 2009) and reovirus (Barton et al, 2001) have been identified.…”
Section: Releasementioning
confidence: 99%